A Numerical Analysis on Coral Larval Networks across Reef Areas on the Northwest Coast of Okinawa Main Island, Japan. Issue 1 (December 2021) - Takeyasu, Kimika; Uchiyama, Yusuke; Zhang, Xu; Matsushita, Kosei; Mitarai, Satoshi
Abstract: Coral bleaching has recently occurred extensively over the world's oceans, primarily due to high water temperatures. Mesophotic corals that inhabit at depths of approximately 30–150 m are expected to survive during bleaching events and to reseed shallow water corals afterward. In particular, in Okinawa, Japan, mesophotic coral ecosystems (MCEs) have been reported to serve as a refuge to preserve genotypic diversities of bleaching-sensitive corals. Connectivity of larval populations between different habitats is a key element that determines the area to be conserved for desirable coral ecosystems. Coral larvae generally behave passively to the surrounding currents and are transported by the advective and dispersive effects of ambient ocean currents. Thus, numerical ocean circulation models enable us to quantify connectivity with detailed spatiotemporal network structures. Our aim in this study is to quantify the short-distance and vertical connectivity of coral larvae in reef areas on the northwest coast of Okinawa Main Island. For the reason that both short-distance and vertical larval transport are influenced by complex nearshore topography, a very high-resolution 3-D circulation model is required. Therefore, we developed a quadruple nested high-resolution synoptic ocean model at a lateral spatial resolution of 50 m, coupled with an offline 3-D Lagrangian particle-tracking model. After validation of the developed model, short-distance horizontal coral connectivity across reef areas on the northwest coast was successfully evaluated. Furthermore, a series of Lagrangian particle release experiments were conducted to identify the vertical coral migration and 3-D connectivity required for the preservation of MCEs. The model revealed that coral larvae released from the semi-enclosed areas tended to remain near the source area, whereas they were diffused and dispersed gradually with time. The mesophotic corals were dispersed vertically to the deeper zone below the mixed layer, while upward transport occurred to induce the mesophotic corals to emerge near the surface, under the influence of the surface mixed layer. The model results solidly indicated significant connectivity between MCEs and shallow coral ecosystems.